MRI of popliteo-meniscal fasciculi of the knee: a pictorial review - Zappia, Marcello; Reginelli, Alfonso; Chianca, Vito; Carfora, Michela; Di Pietto, Francesco; Iannella, Germano; Mariani, Pier Paolo; Di Salvatore, Mariano; Bartollino, Silvia; Maggialetti, Nicola; Cappabianca, Salvatore; Brunese, Luca (Acta Biomedica Atenei Parmensis, 2018)
The popliteomeniscal fascicules (PMFs) provide the attachment of the lateral meniscus to the popliteus musculotendinous region, forming the floor and the roof the popliteal hiatus. In the second half of 1900’s, some anatomic studies claim the important function of the PMF as stabilizers of the lateral meniscus; these anatomical structures work in conjunction with the popliteus musculotendinous unit to prevent excessive lateral meniscal movement and possible meniscus subluxation. A correct diagnosis of the PMFs pathology is crucial to establish the suitable surgical treatment for each patient. MRI is a well-established imaging technique in the musculoskeletal system and the frequency of recognition of normal PMF in the normal knees is high in almost all MRI studies. At day, the gold standard for diagnosis is the arthroscopic evaluation that allows the direct visualization of the popliteo-meniscal ligaments at popliteal hiatus and evaluation of lateral meniscal movements. For this reason if unstable condition of meniscus was suspected, arthroscopic observation with probing into the popliteo-meniscal fascicle area is essential for the identification of the fascicle tears. Despite many treatments have being proposed in literature since now there is high recurrence of knee locking after repair and it is fundamental to develop new surgical techniques in order to achieve better outcome.